#TITLE_ALTERNATIVE# - NUR RACHMAN (NIM : 15309048), ADHITYA
Mud rivers can cause many natural disasters in Indonesia, especially floods. It needs an appropriate technology to minimize the existing pile of mud. One of the solution for this problem is making the river mud as composting material. Mud Ciliwung River has a C/N ratio of 12 with a water content 70% which can potentially be exploited through the composting process. The purpose of this study was to assess the potential of the sludge composting Ciliwung and know the best techniques for making compost composting with mud base material Ciliwung River through aerobic method. Composting method was done by using windrow and passive aerated static pile composting time for 30 days. In the passive aerated static pile method, it is used 2 variations called compost tunnels using bamboo triangle with a size of 160 x 30 x 20 cm and PVC pipes with a size of 160 x 40 x 60 cm. The data were collected by daily monitoring of the compost and laboratory analysis of samples in 0; 3; 6; 9; 12; 15; 18; 22; 25; 30; 33; 37; and 41 days of composting. The results obtained are then compared with SNI 19-7030-2004 standard of quality compost from organic waste compost specifications. Significant temperature rise caused by active windrow method of performance of microorganisms in the composting process with the highest temperature of each piles are 48,5 oC, 38,5 oC, and 39,5 oC. While the aerated static pile, temperatures tend to occur in a stable heap pile. C/N ratio in the windrow method day 41 by 8 while the passive aerated static pile, respectively 11 and 10. This suggests that a better method in maximizing the windrow composting process than the passive aerated static pile. Overall results of the analysis show that the degradation of organic matter sludge Ciliwung River happened. The three composting reactor also produces quality compost that meets almost all parameters contained in SNI 19-7030-2004 on compost quality standards.